2010
DOI: 10.3899/jrheum.090866
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences Between Primary and Secondary Sjögren’s Syndrome

Abstract: A higher frequency of oral symptoms and parotid enlargement and stronger B cell activity (autoantibody production and lymphocyte infiltration) were observed in pSS. Whether these results reflect a true difference between the 2 disease entities or derive from underlying variables remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 31 publications
0
27
1
Order By: Relevance
“…The prevalence of sSS has been reported to range from 4% to 31%, depending on the criteria applied, the methodological design and associated CTD. 23 In our study, there were no differences in the levels of adhesive molecules in pSS and sSS patients. In our opinion, similar elevated serum levels of ICAM, VCAM and E-selectin can be a result of the similar histological pattern in pSS and sSS.…”
Section: Discussioncontrasting
confidence: 52%
“…The prevalence of sSS has been reported to range from 4% to 31%, depending on the criteria applied, the methodological design and associated CTD. 23 In our study, there were no differences in the levels of adhesive molecules in pSS and sSS patients. In our opinion, similar elevated serum levels of ICAM, VCAM and E-selectin can be a result of the similar histological pattern in pSS and sSS.…”
Section: Discussioncontrasting
confidence: 52%
“…It may show as a primary disease without any other accompanying symptoms or as a secondary disease appearing simultaneously with other autoimmune diseases such as rheumatoid arthritis, lupus erythematosus, dermatomyelitis, scleroderma, and primary cirrhosis of the liver. Sjögren syndrome also shows a tendency towards fibromyalgia, migraines, hypothyroidism, Raynaud symptom, and lymphomas [1][2][3][4][5][6][7][8][9][10][11][12]. One of the most bothering symptoms of the syndrome is xerostomia.…”
Section: Discussionmentioning
confidence: 99%
“…Ambiguous results can arise from the different classification of sSS. 28 In our opinion, vasculitis and vasculitic changes are more important issues which should be taken into consideration when VEGF and its isoforms are compared in pSS and sSS. According to Manetti et al, increased plasma levels of VEGF 165 b isoform are associated with the severity of capillary architectural derangement in SSc patients.…”
Section: Discussionmentioning
confidence: 95%
“…Similar clinical, serological and histological features with the exception of perivascular infiltrates in the salivary gland biopsies suggests that pSS and sSS are of the same entity. 28,29 In previous studies, different levels of VEGF and its receptors in SSc and SLE were observed. Ambiguous results can arise from the different classification of sSS.…”
Section: Discussionmentioning
confidence: 98%